Use of Autologous Mesenchymal Stem Cells Derived from Bone Marrow for the Treatment of Naturally Injured Spinal Cord in Dogs - Euler Moraes Penha; Cássio Santana Meira; Elisalva Teixeira Guimarães; Marcus Vinícius Pinheiro Mendonça; Faye Alice Gravely; Cláudia Maria Bahia Pinheiro; Taiana Maria Bahia Pinheiro; Stella Maria Barrouin-Melo; Ricardo Ribeiro-dos-Santos; Milena Botelho Pereira Soares (Stem Cells International)
The use of stem cells in injury repair has been extensively investigated. Here, we examined the therapeutic effects of autologous bone marrow mesenchymal stem cells (MSC) transplantation in four dogs with natural traumatic spinal cord injuries. MSC were cultured in vitro, and proliferation rate and cell viability were evaluated. Cell suspensions were prepared and surgically administered into the spinal cord. The animals were clinically evaluated and examined by nuclear magnetic resonance. Ten days after the surgical procedure and MSC transplantation, we observed a progressive recovery of the panniculus reflex and diminished superficial and deep pain response, although there were still low proprioceptive reflexes in addition to a hyperreflex in the ataxic hind limb movement responses. Each dog demonstrated an improvement in these gains over time. Conscious reflex recovery occurred simultaneously with moderate improvement in intestine and urinary bladder functions in two of the four dogs. By the 18th month of clinical monitoring, we observed a remarkable clinical amelioration accompanied by improved movement, in three of the four dogs. However, no clinical gain was associated with alterations in magnetic resonance imaging. Our results indicate that MSC are potential candidates for the stem cell therapy following spinal cord injury.